Perlindungan Hukum terhadap Anak Pelaku Tindak Pidana Bullying Berdasarkan Undang-Undang Nomor 11 Tahun 2012 - Fadilah, Anwar; Widijowati, Dijan; Sugeng, Sugeng (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Bullying committed by children has become a serious concern within the juvenile justice system in Indonesia. Law No. 11 of 2012 concerning the Juvenile Justice System (SPPA) regulates legal protection for children in conflict with the law, including children who are perpetrators of bullying. This study aims to analyze the form of legal protection provided to children who commit bullying offenses and the application of diversion as the main effort in resolving juvenile cases outside of the judiciary. The research method used is normative juridical with a legislative approach and case study. The results of the study indicate that the SPPA Law prioritizes the principle of restorative justice, emphasizing guidance and rehabilitation for the child offender over criminal sanctions. Diversion becomes the main step in handling cases of children in conflict with the law, except in certain cases that meet the criteria for judicial processes. Therefore, the implementation of legal protection for children who commit bullying must be carried out optimally, considering the principle of the best interests of the child.